Morone saxatilis ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
** Morone saxatilis (Walbaum, 1792). Striped Bass. To about 122 cm (4 ft) TL in eastern Pacific; 183 cm TL (6 ft) in Atlantic. Atlantic and Pacific Oceans—introduced into California; Barkley Sound, British Columbia to just south of U.S. – Mexico border. Anadromous, along beaches and in bays. All in Miller and Lea (1972), as Roccus saxatilis (Walbaum, 1792). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 144, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...